2022
DOI: 10.1155/2022/6422746
|View full text |Cite|
|
Sign up to set email alerts
|

Research on the Throwing Technique of High-Pole Hydrangea Champion Team in the 12th Students’ Games of Guangxi

Abstract: By using the methods of literature, mathematical analysis, and comparative analysis, this study expounds the origin and development history of the culture of Hydrangea and the movement of throwing Hydrangea, studies the representative technical theory of high-pole throwing Hydrangea, and makes a comparative analysis with the angle, speed, and other technical movements of throwing Hydrangea in teaching and training, as well as the trajectory data of the arc top height, circle range, and landing point of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%